The challenge of nursing care to patients with musculoskeletal injury who experience COVID-19: experience report (Research, Society and Development, 2021)
Objective: Report on the nurse's care for patients with musculoskeletal injuries who experience COVID-19. Methodology: Qualitative descriptive approach of the type of experience report that occurred between the months of March and July of 2020, in a national institute of reference for traumatology and orthopedics treatment, located in the city of Rio de Janeiro. Results and discussion: The experience could be narrated through three themes: Flow of caring and the profile of patients seen; Complexity of the care of patients with musculoskeletal injuries who experience COVID-19; New challenges for orthopedic nursing generated by the COVID-19 pandemic. Final considerations: From the perspective of the singularity of care, it was considered complex and challenging to care of the patients who experience, doubly, the musculoskeletal injury and COVID-19. A specialized nursing care during treatment proved to be indispensable as the nurse's action generates a strong bond with the patients, reinforcing compliance to treatment and contributing to the reduction of complications due to coronavirus infection.